Visualized Urethral Mobility Profile During Urine Leakage in Supine and Standing Positions - Zhao, Baihua; Wen, Lieming; Liu, Dan; Huang, Shanya (Ultraschall in der Medizin - European Journal of Ultrasound, 2022)
Objectives To describe the urethral course and position during urine leakage based on the visualized urethral mobility profile (UMP) and to explore the differences between supine and standing positions.Method This was a prospective study of 100 women with SUI and 100 control women who underwent a cough stress test (CST) with transperineal ultrasound (TPUS) in supine and standing positions. In the mid-sagittal plane, the UMP software automatically placed six equidistant points from the bladder neck (point 1) to the external urethral meatus (point 6). It determined the x and y coordinates of the points relative to the symphysis pubis. The distance between the points and symphysis pubis (dist. 1 to 6) was calculated using the formula SQRT (x2 + y2). The visualized UMP was created by reproducing the six points on a bitmap.Results Valid UMP data of 78 control women and 90 women with SUI were analyzed. In the two positions, distances 1 to 6 were significantly greater in the SUI group than the continent group (all p < 0.05). During Valsalva, the distance between the mid-urethra (dist. 3 and 4) and the symphysis was significantly increased (all p < 0.001) in the SUI group. The visualized UMP showed a similar upper-urethral course in the two groups. The gap between the mid-urethra (points 3 and 4) and symphysis was wider in the SUI group.Conclusion The visualized UMP in supine and standing positions showed no difference in the bladder neck and upper urethral stability between incontinent and continent women, but mid-urethral stability was weaker in SUI.
Keywords: Urinary tract; Stress urinary incontinence; Pelvic floor ultrasound; Urethral mobility profile